URGENCY RIJALUL POSTING IN PREVENTING HOAX: QURANIC PERSPECTIVE - Doli Witro (Islamic Communication Journal, 2020)
Indonesian Ministry of Communication and Information stated in 2017 that it had blocked 800 thousand harmful contents, including hoax (fake news). However, Masyarakat Telematika (Mastel) Indonesia reported the results of a survey in 2019 that there were 34.60% of respondents received hoax every day. Hoaxes will have implications for harmony in society and are even very vulnerable to riots. This study uses a qualitative method with a literature review design that study the analogy between hadith and posts of Internet users that are both news or information. Hadith is information from the Prophet p.b.u.h., while posting is information that comes from Internet users. Based on this it is important to see the scholars of hadith in conveying, accepting the hadith, and including it in their respective books. To find out whether or not a hadith is correct, rawi examines sanad and matan hadith. In the hadith science, the study of the hadith discussed in the science of rijalul hadith. In rijalul, this post will be examined on how to explore the content of the Internet media. Of course, this is in accordance with the indicators (adl, dhabit, ittishal al-sanad, bighayr illat, and bighayr syadz) in the science of rijalul hadith, and the perspective of Al-Quran will be examined. Rijalul Posting is divided into two; al-urwah date account (how to clarify posts by looking at the identity and account history) and al-jarh wa ta'dil content account (how to clarify posts). Indicators used: fair information, date of posting, clear source, complete, and polite language. Thus, these posts can be shared on websites or social media.